New dissertation opens the door to exciting and important explanatory models about heritage and the environment.: Review of Susanna Ragnhild Andersdatter Siri’s dissertation, “Cardiovascular risk factors and incidence of acute myocardial infarction and cerebral stroke in Sami and non-Sami populations — The SAMINOR Study”. - Hassler, Sven (Socialmedicinsk tidskrift, 2021)
Susanna Ragnhild Andersdatter Siri’s dissertation on the prevalence of cardiovascular disease in the Sami population in Norway opens the door to exciting and important explanatory models about heredity and the environment. The results show small ethnic differences but are an important reference for continued surveillance in the area. The dissertation was presented at the Center for Sami Health Research, UiT Norway’s Arctic University in Tromsö in September 2020 and was approved for a dissertation on 8 February 2021.